Web-Based Company Workshop Tool Control System (Case Study of Dipo Kereta Malang): Sistem Pengendalian Alat Bengkel Perusahaan Berbasis Web ( Studi Kasus Dipo Kereta Malang) - Harianto, Viqi; Sumarno, Sumarno (Procedia of Engineering and Life Science, 2023)
The management of existing tools at Dipo Kereta Malang in the process of borrowing and returning still uses conventional methods, where employees write in the available books. This can cause problems including a lot of unrecorded data, when at the same time the officer is doing other work. Then, when the process of searching for tool data in a book that takes time. In addition, officers will always check the availability of tools before borrowing. As the role of information and communication technology and the development of tool lending applications to support companies to be more effective. Information technology used includes computer technology to support the loan information system. From the description of the problems above, a web-based tool control system will be created. Website which can be interpreted as a form of group of web pages which can be accessed by everyone and are bound together in one domain. This web-based system can generate information in the form of tool availability, loan reports, and changes in the tool borrowing process where tool borrowing is done the previous day for tomorrow's work. For this reason, employees no longer need to make manual records which are considered less effective and efficient in the future. And with the system created can improve previous shortcomings.